A process for treating wastewater. - Ahmadun, Fakhru'l-Razi; Pendashteh, Alireza (2008)

(untitled)
The present invention relates to a process for treating wastewater. The process includes the steps of (a) mixing different constituents of said wastewater inside a container, (b) withdrawing said wastewater from container, (c) feeding said wastewater to a bioreactor, (d) contacting said wastewater with an isolated microorganism or an isolated microorganism consortium (e) aerating a suspension of said wastewater with said isolated microorganism or said microorganism consortium, (f) withdrawing said suspension of said wastewater with said isolated microorganism or said isolated microorganism consortium from said bioreactor, (g) filtering receiving flow from step (f) to separate a concentrate stream from a permeate stream, (h) returning said concentrate stream to said bioreactor and (i) removing permeate stream.